Combined Operando UV/Vis/IR Spectroscopy Reveals the Role of Methoxy and Aromatic Species during the Methanol‐to‐Olefins Reaction over H‐SAPO‐34. Issue 12 (29th October 2014) - Qian, Qingyun; Vogt, Charlotte; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; Ruiz‐Martínez, Javier; Weckhuysen, Bert M.
Abstract The methanol‐to‐olefins (MTO) process over H‐SAPO‐34 is investigated by using an operando approach combining UV/Vis and IR spectroscopies with on‐line mass spectrometry. Methanol, methoxy, and protonated dimethyl ether are the major species during the induction period, whereas polyalkylated benzenes and polyaromatic species are encountered in the active stage of the MTO process. The accessibility of SAPO‐34 is linked with the amount of methoxy species, whereas the formation of polyaromatic species that block the pores is the main cause of deactivation. Furthermore, the reaction pathways responsible for the formation of olefins and polyaromatics co‐exist and compete during the whole MTO process, and both routes are directly related to the amount of surface polyalkylated benzene carbocations and methoxy species. Hence, a first‐order kinetic model is proposed and comparable activation energies for both processes are obtained.